O ESTATUTO SOCIAL DO SAPATEIRO NA ANTIGUIDADE ATENIENSE - Chevitarese, André Leonardo (PHOÎNIX, 2020)
This paper seeks to analyze the shoemaker's social status in the Athenian archaic and classical periods.